Selangor young voters awareness and motivation during GE14 / Norminaliza Mohamed Azmi and Saraswathy Chinnasamy - Mohamed Azmi, Norminaliza; Chinnasamy, Saraswathy (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2019)
The Malaysian 14th General Election (GE14) in 2018 was an exciting general election which saw high participation from the 'millennials'. Made up 41% from the total Malaysian voters, participation from young voters played a vital role in the changes of Malaysia's political landscape by contributing to the downfall of Barisan Nasional's 60 years administration. Guided by Michael Foucault's theory on power, this paper aimed to assess young voters' awareness towards election issue based on their voting knowledge and dependency on online media platform for information, understanding their voting motivation that led to their participation during the election. Being an urban state in Malaysia with the highest number of voters, Selangor was an ideal selection for the purpose of this paper. Three focus group discussions were conducted amongst twelve (12) Selangor young voters to assess their awareness, motivation and their determination to participate during the election. During discussions, it was found that economic impact issues such as 1 Malaysia Development Berhad (1MDB), Goods and Services Tax (GST), high cost of living, and the National Higher Education Fund Corporation (PTPTN) issue had caught their attention. In addition, their heavy reliance on social media as their source of information had influenced their apolitical decision and the voters were motivated by their desire for a change in a new administration which had led them to cast their votes.